Effects of non-equilibrium plasma and equilibrium discharge on low-temperature combustion in lean propane/air mixtures. (1st May 2023) - Ban, Yangyang; Zhong, Shenghui; Zhu, Jiajian; Zhang, Fan
Highlights: Excited species produced by nonequilibrium plasma, such as O(1D), can promote propane oxidation and propyl (NC3 H7 /IC3 H7 ) production, enhancing the low-temperature reaction pathways. The promoted NC3 H7 /IC3 H7 induced by NRPD offset the low production rate of NC3 H7 O2 /IC3 H7 O2 brought by NTC. The negative temperature coefficient (NTC) phenomenon can be eliminated by non-equilibrium plasma. The higher concentrations of NC3 H7 and HO2 radicals during discharge can lead to advanced intermediate/high temperature reaction processes. Vibrational states and electronic states of N2 and O2 have competitive relationships, leading to a divergent effect on ignition delay time. Abstract: A zero-dimensional (0D) non-equilibrium plasma assisted ignition/combustion (PAI/PAC) model is established by coupling plasma kinetics and combustion kinetics to investigate the effect of non-equilibrium nanosecond repetitively pulsed discharge (NRPD) plasma and equilibrium discharge on low-temperature combustion (LTC) stage of lean propane/air mixtures. The results show that the NRPD case has the fastest ignition, in comparison to equilibrium discharge (ED) with the same discharge energy. With NRPD before LTC, electrons, O( 1 D), as well as O and OH, are formed during discharge, promoting propane consumption dramatically. Electron collision with propane can promote propyls (NC3 H7 /IC3 H7 ) and alkenes, but there is a competitive relationship in terms of discharge energy between them. The formed propyls are mainly consumed to produce propyl peroxyl (NC3 H7 O2 /IC3 H7 O2 ) and accelerate low-temperature product formation, such as ketones and OH. The relaxations of vibrationally excited states are the dominant pathways of heat release, leading to the continuous temperature rising after NRPD. Finally, the negative temperature coefficient (NTC) performances under auto-ignition, NRPD, and ED are investigated. ED only shifts the NTC to the low-temperature zone, while NRPD eliminates the NTC phenomenon. The provided path fluxes of intermediates show that the promoted NC3 H7 /IC3 H7 and NC3 H7 O2 /IC3 H7 O2 induced by NRPD weaken the negative correlation between the oxidation rate of NC3 H7 /IC3 H7 and temperature. The higher concentrations of NC3 H7 /IC3 H7 and HO2 radicals during discharge can result in an advanced intermediate/high temperature reaction process.